A photo-crosslinked hybrid interpenetrating polymer network (IPN) for antibacterial coatings on denture base materials. (15th October 2019) - Cheng, Qiuli; Guo, Xiaowei; Zou, Jiawei; Shi, Xiaoyu; Ding, Shuxiang; Shi, Zuosen; Zhu, Song; Cui, Zhanchen
Abstract : An interpenetrating polymer network (IPN) structured antibacterial layer was prepared on dental base materials using a one-step photo-crosslinking method. Abstract : An interpenetrating polymer network (IPN) structured antibacterial layer was prepared on dental base materials containing quaternary ammonium salt monomers (HMDQAs), polyurethane dimethacrylate oligomers (BIHs) and functionalized SiO2 nanoparticles using a one-step photo-crosslinking method. Scanning electron microscopy (SEM), atomic force microscopy (AFM), ultraviolet near-infrared visible spectrophotometry (UV-3600) and water contact angles were used to study the surface properties of the coatings. SiO2 nanoparticles changed the hydrophilicity of the cationic antimicrobial surface and increased its contact angle. Furthermore, the IPN coatings exhibited highly effective antibacterial activity on the modified dental base material, poly(methyl methacrylate) (PMMA), against Streptococcus mutans, which was evaluated by plate colony counting, optical density (OD), SEM and a live/dead assay. The MTT assay confirmed their biocompatibility. The IPN silicon complexed coating displayed good transparency, excellent antibacterial activity, and no cytotoxicity, which indicated enormous potential for the treatment of denture bases.